Выбор критериев деформируемости при оценке использованного ресурса пластичности в процессах обработки металлов давлением - Огородников, В. А.; Грушко, А. В.; Гуцалюк, А. В. (НТУ "ХПИ", 2014)
В статье приведены результаты исследований пластичности металлов при объемном напряженном состоянии. Обработаны экспериментальные данные о влиянии гидростатического давления и его изменения на пластичность металлов. Показано влияние инвариантов тензора напряжений на пластичность. При этом процесс нагружения образцов рассматривается в пространстве трех безразмерных инвариантных характеристик напряженно-деформированного состояния. Показано, что на пластичность оказывает влияние первая и вторая производная от показателей напряженного состояния. Показано также, что критерии деформируемости, основанные на линейной теории накопления повреждений, дают существенное отклонение между результатами расчета и экспериментом.

The paper presents the results of studies of plasticity of metals at a volume stress. Treated with the experimental data on the effect of hydrostatic pressure and its change on the plasticity of metals. The analyzes were conducted experimental studies of plasticity steels R18, R9, 45. The influence of the invariants of the stress tensor on the plasticity. The process of loading the samples considered in the space of three dimensionless invariant characteristics of the stress-strain state. It is shown that the plasticity is affected first and second derivative of the indicators of stress state. We also show that the deformability criteria based on the linear damage accumulation theory, provide a significant deviation between the calculated and experimental results. Calculations were performed according to the criteria G. A. Smirnov-Alyaev, V. A. Ogorodnikov, V. L. Kolmogorov. In terms of volume stress state on ductility affects the rate of variation of the stress state, and the curvature of the path of deformation.
Selection criteria used in the evaluation of the deformability of the resource of plasticity in metal forming processes
Keywords: критерий; кривизна пути деформирования; ресурс пластичности; траектория деформирования; criterion; curvature of the path of deformation; resource of plasticity; deformation path